2001
DOI: 10.1002/jnr.10051
|View full text |Cite
|
Sign up to set email alerts
|

Reduced postnatal cerebral glucose metabolism measured by PET after asphyxia in near term fetal lambs

Abstract: The effects of fetal asphyxia on cerebral function and development, involve the transition from fetal to neonatal life. Changes in cerebral glucose metabolism may be an early postnatal indicator of fetal asphyxia. The objective is to develop an experimental lamb model involving the transition from fetal to neonatal life and to examine the effect of fetal asphyxia with cerebral hypoxic ischemia on early postnatal cerebral glucose metabolism. Fetal asphyxia was induced by total umbilical cord occlusion in eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…27 A decrease in the uptake of [ 18 F] FDG, to a certain degree, often implies irreversible brain injury. 28 The results of the present study indicated that following HI, glucose metabolism increased and the BG/OC ratio peaked at around 6 -12 hours. Glucose metabolism then decreased with time, and the uptake of [ 18 F] FDG in the whole brain decreased up to 48 -72 hours following HI.…”
Section: Discussionsupporting
confidence: 50%
“…27 A decrease in the uptake of [ 18 F] FDG, to a certain degree, often implies irreversible brain injury. 28 The results of the present study indicated that following HI, glucose metabolism increased and the BG/OC ratio peaked at around 6 -12 hours. Glucose metabolism then decreased with time, and the uptake of [ 18 F] FDG in the whole brain decreased up to 48 -72 hours following HI.…”
Section: Discussionsupporting
confidence: 50%
“…The peak value was 56 (30 -61) kPa, and such a high Pbt O2 has been previously seen only under hyperbaric conditions (18). The finding is probably due to a combination of factors, namely high Fi O2 , postischemic hyperemia accentuated by metabolic and respiratory arterial acidemia, and reduced metabolism (19) in the postasphyctic brain. Surprisingly, Lyng et al (20) found a much smaller peak Pbt O2 in 1-2-d-old piglets that were asphyxiated by breathing an hypoxic mixture and then resuscitated with 30 min of oxygen-ventilation.…”
Section: Discussionmentioning
confidence: 59%
“…15%, in all animals. MAP decreased to a nadir of 14 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) mm Hg in 17 animals and to 32 mm Hg in one. HR decreased to 64 (30 -96) bpm.…”
Section: Resultsmentioning
confidence: 92%
“…Indeed, nutrient source and glucose metabolism of the brain, especially the utilization of ketones, differ in sheep in comparison to human and rodent (Lindsay and Setchell, 1976). This may account for the lack of PET studies in sheep with the notable exception of foetal and neonatal lamb (Thorngren-Jerneck et al, 2001). Additionally, despite studies describing (partially) the functional mapping of the cortex of the sheep (Kirk et al, 1987), from our knowledge, this model has never been used for functional neurosurgery or chronic DBS.…”
Section: Discussionmentioning
confidence: 99%